Praktikalitas Media Pembelajaran Berbasis Wordwall pada Mata Pelajaran Pendidikan Agama Islam Kelas V di SDN 19 Kampung Jawa Kota Solok - Fiqri Rahmad Zeda; Indah Muliati (AS-SABIQUN, 2022)
This articel have a purpose to see the practicality of wordwall-based learning media in the subjects of Islamic Religious Education class V at SDN 19 Kampung Jawa, Solok City. The type of research used in this study is Research and Development with a 4D model modified into 3D, namely 1) Define (definition), 2) Design (design), 3) Develop (development). The results of this study indicate that the wordwall-based learning media has a practical value of 78% on tests conducted on teachers and 98% on tests conducted on students. So it can be concluded that the wordwall-based learning media has proven to be very practical to be used as an interactive media that supports the learning process in the subjects of Islamic Religious Education class V at SDN 19 Kampung Jawa, Solok City.